Spatial variation in mercury concentrations in polar bear (Ursus maritimus) hair from the Norwegian and Russian Arctic - Lippold, Anna; Boltunov, Andrei; Aars, Jon; Andersen, Magnus; Blanchet, Marie-Anne; Dietz, Rune; Eulaers, Igor; Morshina, Tamara N.; Sevastyanov, Vyacheslav S.; Welker, Jeffrey M.; Routti, Heli Anna Irmeli (Science of The Total Environment, 2022)
We examined spatial variation in total mercury (THg) concentrations in 100 hair samples collected between 2008 and 2016 from 87 polar bears (Ursus maritimus) from the Norwegian (Svalbard Archipelago, western Barents Sea) and Russian Arctic (Kara Sea, Laptev Sea, and Chukchi Sea). We used latitude and longitude of home range centroid for the Norwegian bears and capture position for the Russian bears to account for the locality. We additionally examined hair stable isotope values of carbon (δ13C) and nitrogen (δ15N) to investigate feeding habits and their possible effect on THg concentrations. Median THg levels in polar bears from the Norwegian Arctic (1.99 μg g−1 dry weight) and the three Russian Arctic regions (1.33–1.75 μg g−1 dry weight) constituted about 25–50% of levels typically reported for the Greenlandic or North American populations. Total Hg concentrations in the Norwegian bears increased with intake of marine and higher trophic prey, while δ13C and δ15N did not explain variation in THg concentrations in the Russian bears. Total Hg levels were higher in northwest compared to southeast Svalbard. δ13C and δ15N values did not show any spatial pattern in the Norwegian Arctic. Total Hg concentrations adjusted for feeding ecology showed similar spatial trends as the measured concentrations. In contrast, within the Russian Arctic, THg levels were rather uniformly distributed, whereas δ13C values increased towards the east and south. The results indicate that Hg exposure in Norwegian and Russian polar bears is at the lower end of the pan-Arctic spectrum, and its spatial variation in the Norwegian and Russian Arctic is not driven by the feeding ecology of polar bears.